IMPROVING GOVERNMENT INVESTMENT POLICY IN THE AGRICULTURAL SECTOR - Yangiboev Sirojiddin Juromurodovich (American Journals, 2024)
The article explores the economic relationships that arise in the process of attracting and managing investments in the agricultural sector of the region’s economy.
Keywords: Agriculture, investment activity, sectoral development, regional development, efficiency.